Factors influencing poor medication adherence amongst patients with chronic disease in low-and-middle-income countries: a systematic scoping review - Chauke, GD; Nakwafila, O; Chibi, B; Sartorius, B; Mashamba-Thompson, T (Cell Press, 2022)
Background: Poor medication adherence among patients with Chronic Diseases is one of the significant health problems globally. Despite this, evidence on chronic medication adherence in low and middle-income countries is unclear. Objective: This scoping review aimed to identify factors influencing poor medication adherence amongst patients with chronic diseases in low and middle-income countries. Methods: We searched studies exploring factors influencing poor medication adherence amongst patients in low and middle-income countries across the following databases published between 2008 to 2018: Public or publisher Medline, Google scholar, Cumulated Index to Nursing and Allied Health Literature, Health Source, and Medline with full text via Elton B. Stephen's Company host. Methodological quality assessment of the primary studies was done as recommended by Levac, Colquhoun, and O'Brien (2010) review using a Mixed-Method Appraisal Tool 2018. We reported the results following the Preferred Reporting Item for Systematic reviews and Meta-Analyses extension for Scoping Review guidelines. Results: From the initial 154 records screened, we identified six (6) eligible studies that presented evidence on factors influencing poor medication adherence amongst patients in low and middle-income countries. Studies included were from the following countries: Jordan, South Africa, Guatemala, Ethiopia, Indonesia, India, and Palestine. Kappa agreement of the full article screening shows that there was 76.92% agreement versus 58.12% expected by chance which constitutes a considerably good agreement between screeners (Kappa statistic = 0.45 and p-value <0.05). Of the six included studies that underwent methodological quality, five scored 100%, which is regarded as the highest score the remaining one scored between 50–75%, indicating a moderate to low risk bias overall. All included studies presented evidence on medication adherence as being in either knowledge of the diseases, attitudes towards medication taking, beliefs that a patient holds about the treatment or disease, and quality control amongst chronic diseases patients. Conclusions: Our scoping review provides evidence that poor medication adherence in LMICs is influenced by a lack of knowledge, negative attitudes, and negative beliefs, leading to poor quality of life. There is limited research evidence on the effect of patients' beliefs and perceptions on medication adherence in low and middle-income countries. We call upon further research on beliefs, perceptions, and effectiveness of interventions towards chronic medication adherence in low and middle-income countries.